2019
DOI: 10.1111/ele.13342
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting forms of competition set elevational range limits of species

Abstract: How abiotic and biotic factors constrain distribution limits at the harsh and benign edges of species ranges is hotly debated, partly because macroecological experiments testing the proximate causes of distribution limits are scarce. It has long been recognized – at least since Darwin’s On the Origin of Species – that a harsh climate strengthens competition and thus sets species range limits. Using thorough field manipulations along a large elevation gradient, we show the mechanisms by which temperature determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…Since blowfly species are diurnal and N. nepalensis is nocturnal, it is more likely that the presence of maggots influences N. nepalensis behaviour than the presence of adults. The blowfly treatment was conducted by exposing a 75 ± 5 g rat thawed carcass (a previous study showed that 75 g is optimal for offspring production of a pair of N. nepalensis ; Chan et al ) to oriental latrine flies ( Chrysomya megacephala ) in 32 × 32 × 32 cm fly cages for 50 h before the start of each experiment. We chose oriental latrine flies because this species is one of the most abundant species of blowflies in the study region.…”
Section: Methodsmentioning
confidence: 99%
“…Since blowfly species are diurnal and N. nepalensis is nocturnal, it is more likely that the presence of maggots influences N. nepalensis behaviour than the presence of adults. The blowfly treatment was conducted by exposing a 75 ± 5 g rat thawed carcass (a previous study showed that 75 g is optimal for offspring production of a pair of N. nepalensis ; Chan et al ) to oriental latrine flies ( Chrysomya megacephala ) in 32 × 32 × 32 cm fly cages for 50 h before the start of each experiment. We chose oriental latrine flies because this species is one of the most abundant species of blowflies in the study region.…”
Section: Methodsmentioning
confidence: 99%
“…Interspecific species interactions are known to limit the diversity and distribution of species (Bairey, Kelsic, & Kishony, 2016;Bascompte, 2006;Bastolla et al, 2009;Chan, Shih, Chang, Shen, & Chen, 2019;Wisz et al, 2013), to promote species evolution (Ramos & Schiestl, 2019), and to determine ecosystem functions (Brosi & Briggs, 2013;Garibaldi et al, 2013). Much progress was made in understanding the structure and dynamics of species interaction networks (Bastolla et al, 2009;Blüthgen, Menzel, & Blüthgen, 2006;Olesen, Bascompte, Dupont, & Jordano, 2007;Petanidou, Kallimanis, Tzanopoulos, Sgardelis, & Pantis, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…6, sensu ref. 32 ). During summer, we found a significant interaction between mountain range and the source population being transplanted.…”
Section: Resultsmentioning
confidence: 99%
“…To estimate beetle densities and determine breeding phenology at each site, we averaged the number of beetles by month because we replicated the experiments for~3 years. Adult burying beetles were collected using hanging pitfall traps baited with rotting pork 32,60 Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation